Criminal responsibility for fraud and imitation of medicines and medical preparations - Maytham Falih Hussein ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The forms of dealing with medicines and medical preparations is governed by legal rules. If the transaction becomes a violation of the law، then it constitutes a criminal behavior that deserves punishment، protecting the interest، thehuman right to the safety of his body and to preserve the national economy. Therefore، fraud and imitation of medicines and medical preparations arecrimes that have specific criminal penalties in the comparative legislation and Iraqi legislation.